IMPROVING AGRICULTURAL PRODUCTIVITY: INNOVATION AND SUSTAINABLE APPROACHES TO EFFICIENT PRODUCTION (American Journal of Interdisciplinary Research and Development, 2024)
Agricultural productivity plays an important role in ensuring global food security and sustainable development. This research paper explores various innovative approaches and sustainable practices to increase agricultural production. We will explore technological advances, precision agriculture, genetic engineering, agroecology and sustainable resource management strategies to address the challenges facing the agricultural sector. By adopting these practices, we can optimize productivity, reduce environmental impact, and contribute to the development of resilient and sustainable food systems.